pathterminuspages/brkmnd.dk/aboutcontactabout me

Geometrisk serie

30-09-2017|Sumfølger

Geometrisk sumfølge er givet som: $$\sum_{k=0}^{n}{x^k} = \frac{x^{n+1} - 1}{x - 1}$$ Hvor $x \neq 1$.

Bevis

Induktionsstart

$n_0 = 0$ : $x^0 = 1 = \frac{x^1 - 1}{x - 1}$
$n_0 = 1$ : $x^0 + x^1 = x + 1 = \frac{x^2 - 1}{x - 1} = \frac{(x - 1)(x + 1)}{x - 1}$

Induktionsskridt

Lad $$\sum_{k=0}^{n}{x^k} = \frac{x^{n+1} - 1}{x - 1}$$ Vi får $$ \sum_{k=0}^{n}{x^k} + x^{n + 1} = \\ \frac{x^{n+1} - 1}{x - 1} + x^{n + 1} = \\ \frac{x^{n+1} - 1 + (x - 1) x^{n+1}}{x - 1} = \\ \frac{x^{n+1} - 1 + x^{n+2} - x^{n+1}}{x - 1} = \\ \frac{x^{n+2} - 1}{x - 1} $$

Og vi har vist hvad vi skulle.